Construction of Growth Model for Mandarin Fish (Siniperca chuatsi) Guangqing No.1 fed with Compound Diet and cultivated in Pond - Fubao WANG; Guangzhao CHENG; Junjian DONG; Chengfei SUN; Miao WANG; Maixin LU; Xing YE (Guangdong nongye kexue, 2022)
【Objective】The study was conducted to understand the growth and development law of Siniperca chuatsi Guangqing No.1 (hereinafter called mandarin fish) fed with compound diet and cultivated in pond so as to provide references for the breeding and large-scale culture of mandarin fish.【Method】The morphological parameters and growth performance of mandarin fish fed with compound diet at different month-ages in a whole cultivation period were measured. Three nonlinear models, Logistic, Gompertz and Bertalanffy, were used to construct the growth curves of both body mass and body length of the mandarin fish.【Result】The maximum absolute body weight gain and absolute body length gain were found at 5-month-age fish, and 3-month-age fish, respectively. While the relative body weight gain and body length gain began to decrease from 4 months age. Morphological parameters, including condition factor (CF), viscerosomatic index (VSI) and mesenteric fat index (MFI) increased while hepatosomatic index (HIS) and intestine & stomach index (ISI) decreased as the fish month ages increased. The three models could simulate the growth curve of mandarin fish well, with a degree of fit R2 ≥ 0.97. Correlation analysis between the model predicted value and the measured value showed that the Logistic model was better than the other two models. The growth models for body mass and both length were as follows respectively, Wt=1230.808/(1+39.666e-0.760t), R2=0.989; Lt=40.871/(1+3.076e-0.387t), R2=0.990. The growth inflection point for body mass was at 4.843 months, corresponding to body mass and both length of 615.404 g and 20.436 cm, respectively.【Conclusion】Logistic model is more suitable to describe the growth process of mandarin fish, and it can predict the growth data of different stages, which will provide theoretical basis for further breeding and large-scale culture of mandarin fish fed with compound diet.